Creative blogging : your first steps to a successful blog - Wright-Porto, Heather (Apress ; Distributed to the Book trade worldwide by Springer Science+Business Media, 2011)
Creative Blogging shows you how to start blogging for the very first time to express your creativity, reach out and be heard - and even how to make money with your blog!. You'll start at the right place: The beginning! Learn answers to the most important and popular questions: What is a blog? Do I need a blog? How do I get started? What do I blog about? How do I blog? Creative Blogging then takes you through the how-to aspects of blogging, so you can quickly learn the terminology and get started. You'll then be able to choose the right blogging tool for you!. Soon, you'll be prepared to unleas.